2021
DOI: 10.5005/jp-journals-10071-23806
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on the Emotional Well-being of Healthcare Workers: A Multinational Cross-sectional Survey

Abstract: A bstract Background Coronavirus disease-2019 (COVID-19) in the last few months has disrupted the healthcare system globally. The objective of this study is to assess the impact of the COVID-19 pandemic on the psychological and emotional well-being of healthcare workers (HCWs). Materials and methods We conducted an online, cross-sectional, multinational survey, assessing the anxiety (using Generalized Anxiety Disorder [GAD-2] and GAD-7), depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Psychological distress of healthcare workers also exists in the COVID-19 era. Previous studies reported that a high proportion of healthcare workers are experiencing significant levels of anxiety, depression, insomnia, and distress during the COVID-19 pandemic (11)(12)(13)(14)(15). The rates were broadly reported to range between 23.2 and 67.55% for anxiety, 22.8-55.89% for depression, and 34.0%-68.7% for insomnia.…”
Section: Stress Anxiety and Quality Of Lifementioning
confidence: 99%
“…Psychological distress of healthcare workers also exists in the COVID-19 era. Previous studies reported that a high proportion of healthcare workers are experiencing significant levels of anxiety, depression, insomnia, and distress during the COVID-19 pandemic (11)(12)(13)(14)(15). The rates were broadly reported to range between 23.2 and 67.55% for anxiety, 22.8-55.89% for depression, and 34.0%-68.7% for insomnia.…”
Section: Stress Anxiety and Quality Of Lifementioning
confidence: 99%
“…With a prevalence of 21% (95CI = [5; 37]) before 2020 and 35% (95CI = [33; 37]) after 2020 (Table 3 and Additional file 6 ), depression, as anxiety, seemed to be more prevalent in HCW compared to the overall population [ 115 , 116 ], among frontliners [ 5 , 55 , 74 , 77 , 117 124 ], those caring for patients [ 81 , 125 127 ], especially for COVID-19 patients, and even on HCW that had become infected [ 50 , 67 , 77 , 88 , 88 , 98 , 109 , 125 , 128 130 ]. Female gender was also mentioned to be related with depression [ 51 , 66 , 71 , 74 , 80 , 86 88 , 88 , 93 , 98 , 122 , 128 , 129 , 131 136 ].…”
Section: Resultsmentioning
confidence: 99%
“…Depression was the second outcome most frequently addressed (N = 503). With a prevalence of 21% (95CI= [5;37]) before 2020 and 35% (95CI= [33;37]) after 2020 (Table 3 and additional le 6), depression, as anxiety, seemed to be more prevalent in HCW compared to the overall population (115,116), among frontliners (5,55,74,77,(117)(118)(119)(120)(121)(122)(123)(124), those caring for patients (81, 125-127), especially for COVID-19 patients, and even on HCW that had become infected (50,67,77,88,88,98,109,125,(128)(129)(130). Female gender was also mentioned to be related with depression (51, 66, 71, 74, 80, 86-88, 88, 93, 98, 122, 128, 129, 131-136).…”
Section: Resultsmentioning
confidence: 99%